The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s40267-016-0299-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring polypharmacy at the population level entails complex decisions: results of a survey of experts in geriatrics and pharmacotherapy

Abstract: Aim The use of multiple medications is rising steadily among older individuals, but little is known about the impact of polypharmacy at a population level, both over time and across countries. Surveillance of polypharmacy is required to overcome these gaps. There currently exists no standard population indicator of polypharmacy. The objective of this survey was to query expert opinion on establishing a gold standard method for polypharmacy surveillance at the population level. Methodology We invited 71 experts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…Our ndings provide guidance for the inclusion of other medication-related factors, including use of high risk medicines and inappropriate medication duplication when developing future polypharmacy tools and deprescribing guidelines. These results align with recent literature which has suggested to look beyond simply the number of medicines and incorporate the concept of the quality of prescribing by considering speci c types of medicines and inappropriate medication duplication to assess polypharmacy appropriateness [10,21,[28][29][30][31]. Additionally, these ndings provide guidance for identifying patients who may require a comprehensive review of their medicines such as a home medicines review (HMR) by a pharmacist [32].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our ndings provide guidance for the inclusion of other medication-related factors, including use of high risk medicines and inappropriate medication duplication when developing future polypharmacy tools and deprescribing guidelines. These results align with recent literature which has suggested to look beyond simply the number of medicines and incorporate the concept of the quality of prescribing by considering speci c types of medicines and inappropriate medication duplication to assess polypharmacy appropriateness [10,21,[28][29][30][31]. Additionally, these ndings provide guidance for identifying patients who may require a comprehensive review of their medicines such as a home medicines review (HMR) by a pharmacist [32].…”
Section: Discussionsupporting
confidence: 80%
“…Our ndings further con rm this process from the perspective of a large number and range of clinicians. Previous studies of clinical experts in geriatric medicine have found strong consensus regarding considering medicationrelated factors such as the use of high-risk medicines including benzodiazepines and antipsychotics as well as inappropriate duplication of medicines in addition to the medicines count for polypharmacy rationalisation [21,30,33]. Our ndings combined with previous literature provide guidance for pharmacists undertaking home medicines reviews in the community and nursing home settings and clinicians undertaking medication reviews in the hospital setting, to identify medicines commonly associated with harm and exploring the possibility of deprescribing them.…”
Section: Discussionmentioning
confidence: 99%
“…However, polypharmacy is challenging to address. There is a lack of clarity concerning what is the appropriate treatment of multi-morbidity, and what is overprescription with potentially harmful outcomes [17]. Clinicians often lack direction in this area, as guidelines generally focus on one or a cluster of disorders rather than polypharmacy specifically [49].…”
Section: Discussionmentioning
confidence: 99%
“…This entails documenting changes in the prevalence of dispensation, as well as clinical prescription patterns—including the source of prescription, treatment duration, and use of other central nervous system (CNS) drugs. CNS polypharmacy is of particular importance, as the safety and efficacy of combining psychotropic drug classes are not well established [17], with adverse effects including cumulative toxicity and drug interactions [18]. A US population-based study found that psychotropic polypharmacy of two drugs was associated with a 17% higher average number of side effects, while polypharmacy with three or more drugs was associated with a 38% higher average number, compared with monopharmacy [19].…”
Section: Introductionmentioning
confidence: 99%
“…As both adult ADHD and the aforementioned comorbid disorders feature a chronic, long-lasting course, it may result in long treatment periods with simultaneous use of multiple medications. Although use of multiple medications has been associated with increased risks of adverse drug events, including nonadherence, cumulative toxicity, and drug–drug interactions ( Sarkar, 2017 ; Sirois et al, 2016 ), very little is known about comedication and polypharmacy patterns associated with ADHD medication. Moreover, there is limited information on how to address comedication in treatment guidelines for ADHD ( National Institute for Health and Care Excellence [NICE], 2018 ; Swedish National Board of Health and Welfare [Swedish: Socialstyrelsen], 2014 ; Wolraich et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%